Technique for Physically Managing Urban Slums - Yusli Kukuh; Sitti Bulkis; Kurniaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
According to the Gowa Regent's Decree on Determining the Location of Slum Housing and Slum Settlement in Sungguminasa Village, Sungguminasa Village has a total area of 17.7 Ha in 2020, with a moderate degree of slums. As a result, the purpose of this research is to explain the features of the socioeconomic and physical components, as well as to build a handling plan in compliance with PERMEN PUPR No. 2 of 2016. Field observations, expert interviews, and related literature were used to collect data. The respondents were chosen using a basic random sampling procedure. The scoring analysis, quantitative descriptive, and correlation tests were employed in the analysis. The study's findings show that the rise of slums in Sungguminasa Village is driven by a physical factor, specifically the current state of inadequate environmental drainage. And the socioeconomic factor, namely personal income, has a mild negative impact on the level of slums; that is, the greater the personal money obtained by the community through employment, the lower the level of slum in Sungguminasa Village.